2005
DOI: 10.1164/rccm.200409-1220oc
|View full text |Cite
|
Sign up to set email alerts
|

The CXCL10/CXCR3 Axis Mediates Human Lung Mast Cell Migration to Asthmatic Airway Smooth Muscle

Abstract: Mast cell microlocalization within the airway smooth muscle bundle is an important determinant of the asthmatic phenotype. We hypothesized that mast cells migrate toward airway smooth muscle in response to smooth muscle-derived chemokines. In this study, we investigated (1) chemokine receptor expression by mast cells in the airway smooth muscle bundle in bronchial biopsies from subjects with asthma using immunohistology, (2) the concentration of chemokines in supernatants from stimulated ex vivo airway smooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
301
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(314 citation statements)
references
References 40 publications
9
301
1
3
Order By: Relevance
“…Indeed, a recent study has demonstrated that tryptase-stimulated human ASM cells attract mast cells through the release of TGF-␤1 in addition to SCF, and that both factors are localized to ASM in asthmatic airways (11). Another recent study has shown that the chemokine CXCL10 (IFN-␥-inducible protein 10) is expressed preferentially by asthmatic ASM cells, and its receptor CXCR3 is most abundantly expressed on mast cells in asthmatic ASM, suggesting that interactions between ASM-derived CXCL10 and mast cell-expressed CXCR3 may play a key role in mast cell migration into the ASM bundles in asthma (40). Tryptase cleavage of eotaxin and RANTES may therefore not have an impact on mast cell microlocalization in asthmatic ASM.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study has demonstrated that tryptase-stimulated human ASM cells attract mast cells through the release of TGF-␤1 in addition to SCF, and that both factors are localized to ASM in asthmatic airways (11). Another recent study has shown that the chemokine CXCL10 (IFN-␥-inducible protein 10) is expressed preferentially by asthmatic ASM cells, and its receptor CXCR3 is most abundantly expressed on mast cells in asthmatic ASM, suggesting that interactions between ASM-derived CXCL10 and mast cell-expressed CXCR3 may play a key role in mast cell migration into the ASM bundles in asthma (40). Tryptase cleavage of eotaxin and RANTES may therefore not have an impact on mast cell microlocalization in asthmatic ASM.…”
Section: Discussionmentioning
confidence: 99%
“…The location of mast cells within the ASM is believed to facilitate hyper- [26,27]. ASM cells also produce SCF, which itself induces mast cell recruitment, differentiation and survival [28].…”
Section: Asthmamentioning
confidence: 99%
“…ASMs from individuals with asthma exhibit increased synthetic capacity (8,9), mitochondrial biogenesis (10), altered calcium homeostasis (10,11), and in some reports (10)(11)(12), but not all (13,14), increased proliferation. Critically, there is emerging evidence that ASM from individuals with asthma is hypercontractile as demonstrated by an increased velocity of contraction in response to electrical field stimulation at the single-cell level (15) and in cell populations using gel contraction assays (16).…”
mentioning
confidence: 99%